Livestock keeping in the tsetse belt of West Africa - International Livestock Research Institute (International Livestock Research Institute, 2011)
Across Africa the disease trypanosomosis kills millions of livestock annually. Over the last 60 years many strategies have been tried for dealing with the disease, with limited success. The most common method is to use drugs called trypanocides to treat and prevent disease. Now resistance to these drugs is developing, making it increasingly difficult to control trypanosomosis over ever growing areas. Rational Drug Use is a new approach that aims to minimize the emergence and spread of resistance to trypanocides. By promoting good practices tested in human health, it aims to improve treatments and animal health. But with over 50 million doses of trypanocides being given to cattle annually, is this too little, too late? This is one of three films telling the story of the current state of the war against a disease that is so deadly and widespread that farmers call it "the malaria of cattle'.